An Investigation of Some New Tree Structures - Woodford, Brenda (My University, 1977)
A study of the tree structures developed by Finkel and Bentley (3 & 4) was done and the results are documented in this report. These tree structures, i.e. the quad tree and the k-d tree, were especially developed for associative retrieval. A comparison of the above tree structures and the well known binary search tree is presented for exact match queries.
An implementation of the insertion algorithms for each tree structure and a generalization of Aldon Walker's (9) display algorithm are given.
Keywords: Library and Information Science; Library and Information Science